Project-based learning in physical education and sport (2020-2025): a systematic review of teaching approaches and student learning outcomes - Gemi Candra; Jeki Haryanto (Journal of Educational and Learning Studies, 2026)
Project-Based Learning (PjBL) as a student-centred, inquiry-driven pedagogy has been widely accepted. However, its implications in physical education (PE) and sport have not been fully explored and vary across different contexts. This systematic literature review consolidates findings from different studies that have looked into PjBL in PE and sport-related educational settings and the effect it has on learning outcomes. The review adhered to the PRISMA 2020 framework and a structured Scopus search was performed which initially identified 682 records. Subsequently, duplicates and records ineligible due to document-type, language, and subject-area limiters were removed. Title and abstract screening was followed by full-text eligibility assessment against pre- defined criteria resulted in 14 studies published between 2020 and 2025. Empirical studies employing PjBL in physical education, sport, or coaching settings (2020–2025) were eligible; the 14 retained studies resulted from criterion-based screening rather than a predetermined target. Methodological quality was appraised with the FICO framework (threshold 3.0/4.0), and screening decisions were checked for reviewer agreement. Synthesis was thematic (interpretive) rather than meta-analytic. The thematic synthesis yielded three main findings: PjBL is executed through a variety of ways such as classroom projects, teacher-training tasks, and work- based coach development; it leads to improvements in cognitive, psychomotor, and affective outcomes, including collaboration and self-confidence; however, implementation is limited by remaining barriers such as inadequate facilities, time, and teacher readiness. This review of literature contributes to sport pedagogy by revealing PjBL practice and outcomes, gives a guide to the practitioners, offers practical help to the teachers and coaches, and encourages larger, longitudinal, and methodologically rigorous studies